The Effect of Company Size, Capital Structure, and Profitability on Company Value in Transportation Companies Listed on The Indonesian Stock Exchange Period 2021-2023 - Ni Putu Ari Ratmiasih; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Effective and efficient utilization of company resources is essential to demonstrate the condition of a company, which is usually presented in financial reports. This study aims to explain the effect of company size, capital structure, and profitability on company value in transportation companies listed on the Indonesia Stock Exchange for the period 2021-2023. The population used in this study is transportation companies listed on the Indonesia Stock Exchange. The sample in this study uses all transportation companies on the Indonesia Stock Exchange from 2021 to 2023 with a saturated sampling technique. The analysis method used in this study is multiple linear regression analysis. The results of this study indicate that company size, capital structure, and profitability in transportation companies have a significant positive effect on company value. Suggestions for further research include developing this study by adding variables and company sectors.